2002
DOI: 10.1002/mrd.10193
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel GPI‐anchored CRISP glycoprotein, MAK248, located on the posterior head and equatorial segment of cynomolgus macaque sperm

Abstract: To identify a sperm-surface component that is highly antigenic, we immunized female cynomolgus macaques with glycosylphosphatidylinositol (GPI)-anchored sperm surface proteins that were released following treatment with phosphatidylinositol-specific phospholipase C (PI-PLC). Five different adjuvants were used in combination with the PI-PLC-released proteins, and three of these proteins (24, 48, and 53 kDa) were shown to be potent antigens for immunization of female monkeys. The 53 kDa protein was found to be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 87 publications
1
23
0
Order By: Relevance
“…In contrast, our results suggest that HrUrabin plays a pivotal role in the primary binding of sperm to HrVC70, a sperm receptor on the VC, rather than gamete fusion, during fertilization. In macaque, it is reported that an antibody raised against sperm surface protein, which is released by treatment with PI-PLC, revealed the existence of GPI-anchored CRISP on the sperm membrane, possibly participating in fertilization (25). This protein exists in two isoforms with molecular masses of 24 and 48 kDa, similarly to HrUrabin, although they assumed that the 48-kDa isoform is a dimer of the 24-kDa isoform (25).…”
Section: Difference In the Results By Far Western Analysis And Yeastmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, our results suggest that HrUrabin plays a pivotal role in the primary binding of sperm to HrVC70, a sperm receptor on the VC, rather than gamete fusion, during fertilization. In macaque, it is reported that an antibody raised against sperm surface protein, which is released by treatment with PI-PLC, revealed the existence of GPI-anchored CRISP on the sperm membrane, possibly participating in fertilization (25). This protein exists in two isoforms with molecular masses of 24 and 48 kDa, similarly to HrUrabin, although they assumed that the 48-kDa isoform is a dimer of the 24-kDa isoform (25).…”
Section: Difference In the Results By Far Western Analysis And Yeastmentioning
confidence: 99%
“…In macaque, it is reported that an antibody raised against sperm surface protein, which is released by treatment with PI-PLC, revealed the existence of GPI-anchored CRISP on the sperm membrane, possibly participating in fertilization (25). This protein exists in two isoforms with molecular masses of 24 and 48 kDa, similarly to HrUrabin, although they assumed that the 48-kDa isoform is a dimer of the 24-kDa isoform (25). As mentioned above, CRISP members on the sperm surface seem to play diverse roles in fertilization in different species.…”
Section: Difference In the Results By Far Western Analysis And Yeastmentioning
confidence: 99%
“…Cynomolgus macaque sperm have a constituent population of GPI-anchored (glyco)proteins that are released after exposure to phosphatidylinositol-specific phospholipase C (PI-PLC) [18]. Because this group of membrane proteins is completely exposed to the external environment, they have been used to elicit an isoimmune response in female macaques [18].…”
Section: Introductionmentioning
confidence: 99%
“…Because this group of membrane proteins is completely exposed to the external environment, they have been used to elicit an isoimmune response in female macaques [18]. Following immunization with these PI-PLC-released proteins, together with five different adjuvants, only two glycoproteins (24 and 53 kDa) were consistently recognized as potent isoantigens [18]. The 24-kDa protein was found to be a GPI-anchored CRISP glycoprotein called MAK248, and it has been described in detail previously [18].…”
Section: Introductionmentioning
confidence: 99%
“…This 35-kDa GPI-anchored glycoprotein, referred to as HrUrabin (Halocynthia roretzi unique lipid rafts-derived binding partner), showed a sequence homology to a CRISP (Cys-rich secretory protein) family, some members of which are known to play roles in fertilization (Yudin et al, 2002;Ellerman et al, 2006;Roberts et al, 2006). We showed that HrUrabin also has a function in fertilization, since an antibody against HrUrabin specifically inhibited fertilization.…”
Section: Hrurabin a Sperm Binding Partner Of Hrvc70mentioning
confidence: 85%